Wartan Rubenowicz Grigorian (1929-2019) - Aram Grigorian (Ksiegarnia Akademicka Publishing, 2021)
Vartan Rubenovich Grigoryan: historian, armenologist, publicist,collector of ancient Armenian manuscripts (1929-2019)